2016
DOI: 10.1002/xrs.2727
|View full text |Cite
|
Sign up to set email alerts
|

Increased zinc accumulation in mineralized osteosarcoma tissue measured by confocal synchrotron radiation micro X-ray fluorescence analysis

Abstract: Abnormal tissue levels of certain trace elements such as zinc (Zn) were reported in various types of cancer. Little is known about the role of Zn in osteosarcoma. Using confocal synchrotron radiation micro X‐ray fluorescence analysis, we characterized the spatial distribution of Zn in high‐grade sclerosing osteosarcoma of nine patients (four women/five men; seven knee/one humerus/one femur) following chemotherapy and wide surgical resection. Levels were compared with adjacent normal tissue. Quantitative backsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…Recent SR XRF studies also targeted osteosarcoma-the most common bone cancer in children and teens in which tumor cells produce immature bone also known as osteoid (the un-mineralized organic part of the bone matrix during bone formation). As reported by Rauwolf et al [85] and Streli et al [86], the Zn levels in the bone regions affected by osteosarcoma were found to be significantly higher than those in the healthy regions within the same bone sample. On average, the Zn fraction median in osteosarcoma regions, defined as the median of the relative counts ratio Zn/(Zn + Ca) distribution, was found to be about six times higher than that measured in healthy bone regions.…”
Section: Bone Teeth and Internal Organssupporting
confidence: 66%
See 2 more Smart Citations
“…Recent SR XRF studies also targeted osteosarcoma-the most common bone cancer in children and teens in which tumor cells produce immature bone also known as osteoid (the un-mineralized organic part of the bone matrix during bone formation). As reported by Rauwolf et al [85] and Streli et al [86], the Zn levels in the bone regions affected by osteosarcoma were found to be significantly higher than those in the healthy regions within the same bone sample. On average, the Zn fraction median in osteosarcoma regions, defined as the median of the relative counts ratio Zn/(Zn + Ca) distribution, was found to be about six times higher than that measured in healthy bone regions.…”
Section: Bone Teeth and Internal Organssupporting
confidence: 66%
“…More detailed synchrotron-based XRF data and more in-depth relationships with bone and joint anatomy, physiology, and histopathology were revealed and discussed in several papers published by an extended European research collaboration over the past 15 years [82][83][84][85][86]. A common denominator of these bone studies is the comparison of the synchrotron-based XRF elemental imaging and analysis with the images obtained from quantitative backscattered electron imaging (qBEI)-a scanning electron microscope (SEM) technique developed in the 1990s [87] which measured Ca concentration at a few micrometers spatial resolution based on a calibration with grey scale values from SEM images.…”
Section: Bone Teeth and Internal Organsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, very little is known about the distribution of Gd in bone on the microscopic level. Our group has already employed the method of synchrotron radiation induced micro-X-ray fluorescence (SR-micro-XRF) for the characterization of distribution of trace elements, such as lead (Pb), zinc (Zn) and strontium (Sr) in healthy and diseased bone and cartilage samples [20][21][22] . Within this project we applied SR-micro-and submicro-XRF for the detection and mapping of Gd distribution within bone tissue.…”
mentioning
confidence: 99%
“…Such research has provided insights into biogenic “baselines” and metabolic patterns of TE accumulation in bone and dental tissues (Kang et al 2004 ; Zoeger et al 2005 , 2008 ; de Souza-Guerra et al 2010 , 2014 ; Pemmer et al 2013 ; Wang et al 2017 ). Use of SR-XFI to map the disproportionate distribution of TEs such as Pb and Zn in modern bone with respect to diseases such as osteoarthritis and osteosarcomas (Zoeger et al 2008 ; Rauwolf et al 2017 ) may also aid in palaeopathological interpretations, potentially including cases where the diseases were still in early stages at death. Overall, research in this area has produced several valuable takeaways for the bioarchaeological interpretation of TE variation within specific developmental junctures.…”
Section: Resurgence Of Trace Element Analysis? Techniques With Growinmentioning
confidence: 99%